Spectral evidence for emergent order in Ba1−xNaxFe2As2 - Yi, M.; Frano, A.; Lu, D. H.; He, Y.; Wang, Meng; Frandsen, B. A.; Kemper, A. F.; Yu, R.; Si, Q.; Wang, Liran; He, M.; Hardy, F.; et al. (Physical review letters, 2018)
We report an angle-resolved photoemission spectroscopy study of the iron-based superconductor family, Ba1−xNaxFe2As2. This system harbors the recently discovered double-Q magnetic order appearing in a reentrant C4 phase deep within the underdoped regime of the phase diagram that is otherwise dominated by the coupled nematic phase and collinear antiferromagnetic order. From a detailed temperature-dependence study, we identify the electronic response to the nematic phase in an orbital-dependent band shift that strictly follows the rotational symmetry of the lattice and disappears when the system restores C4 symmetry in the low temperature phase. In addition, we report the observation of a distinct electronic reconstruction that cannot be explained by the known electronic orders in the system.
Im Titel erscheinen die Zeichen 1-x, x und 2 jeweils tiefgestellt
Gesehen am 22.04.2020